Mammalian Carnivores of Florida - Raoul K Boughton; Bethany Rose Wight; Elizabeth Pienaar; Martin B Main (EDIS)
Florida is home to several species of animals in Order Carnivora, a group of mammals with teeth adapted to allow them to eat meat. Many of them, like panthers, you probably know about, and some, like raccoons, you may see regularly. But did you know Florida hosts two separate species of foxes? Two different skunks? Weasels? This 20-page fact sheet written by Raoul Boughton, Bethany Wight, Elizabeth Pienaar, and Martin B. Main and published by the UF/IFAS Department of Wildlife Ecology and Conservation provides an overview of the mammalian carnivores of Florida from panthers to mink. https://edis.ifas.ufl.edu/uw464